Detailed National Accounts, SNA 2008: Simplified non-financial accounts (Edition 2019) (OECD National Accounts Statistics, 2008)
This comparative table includes statistics on simplified non-financial accounts, from the gross value added to the net lending/net borrowing.The core simplified non-financial accounts correspond to generation of income account, distribution of income account, use of disposable income account and capital account. Data are internationally comparable with respect to the System of National Accounts 1993(SNA 1993) and are available from 1950 onwards